Imaging the Igorot vernacular films produced in the Cordillera - Tindaan, Ruth M. (2010)
This study analyzes the images of the Igorot in vernacular films produced by Igorot filmmakers in the Northern Luzon Cordillera. Employing a postcolonial framework, the study proposes that this body of self-representative work gives confidence to the Igorot community to tell their own stories which have been ignored, misunderstood, or misrepresented from colonial to contemporary times. With semiotics as analytical tool, this study first examines the images of the Igorot in Philippine mainstream films. The study points out that the master tropes of animalization and intellectual infancy generally describe the prevailing image of the Igorot in mainstream cinema. In an attempt to show the potential of vernacular films as counter-discourse to mainstream cinema, the study also submits the vernacular films to a semiotic examination. Vernacular films are shown confronting mainstream stereotypes by foregrounding Igorot agency and collective action. The study concludes, however, that despite the constructive images that they create, the vernacular films fall short of truly reformulating stereotypical images of the Igorot in mainstream cinema because they reinforce dominant misconceptions about the Igorot. These films therefore fail to produce a more complex representation of the Igorot community or to lay the foundations of an empowered Igorot cinema.
Keywords: Igorot (Philippine people) -- Pictorial works; Igorot (Philippine people) -- Exhibitions; Filmmaking; Documentary films -- Production and direction